Time–frequency multiresolution of fault-generated transient signals in transmission lines using a morphological filter - Quispe Huarcaya, Juan Carlos (2023)
The ongoing transformation of electrical power systems highlights the weaknesses of the protection schemes of traditional devices because they are designed and confgured according to traditional characteristics of the system. Therefore, this work proposes a new methodology to study the fault-generated high frequency transient signals in transmission lines through multiresolution analysis. The high frequency components are determined by a new digital fltering technique based on mathematical morphology theory and a spectral energy index. Consequently, wide spectra of signals in the time–frequency domain are obtained. The performance of this method is verifed on an electrical power system modeled in ATP-Draw, where simulation and test signals are developed for diferent locations, fault resistances, inception angles, high frequency noises, sampling frequencies, types of faults, and shapes of the structuring element. The results show the characteristics of the fault such as the traveling wave frequency, location, and starting time.